Exploring the Association Between Cervical Microbiota and HR-HPV Infection Based on 16S rRNA Gene and Metagenomic Sequencing - Fang, Bingyan; Li, Qun; Wan, Zixian; OuYang, Zhenbo; Zhang, Qiushi (Frontiers in Cellular and Infection Microbiology, 2022)
The relationship between the cervico-vaginal microbiome and high-risk human papillomavirus (HR-HPV) is well observed. However, there is a lack of adequate research regarding the cervical microbiota in HR-HPV infection. Most published research results have used 16S rRNA gene sequencing technology; this technology only focuses on marker sequences, resulting in incomplete gene information acquisition. Metagenomic sequencing technology can effectively compensate for the deficiency of 16S rRNA gene sequencing, thus improving the analysis of microbiota function. Cervical swab samples from 20 females with HR-HPV infection and 20 uninfected (Control) women were analyzed through 16S rRNA gene and metagenomic sequencing. Our results indicated that the composition and function of the cervical microbiota of HR-HPV infection differed notably from that of control women. Compared with control women, Firmicutes was decreased during HR-HPV infection, whereas Actinobacteria was increased. At the genus level, Lactobacillus was enriched in control women, while levels of Gardnerella and Bifidobacterium were lower. At the species level, Lactobacillus crispatus, L. jensenii, and L. helveticus were enriched in control women; these were the top three species with biomarker significance between the two groups. Eight pathways and 30 KEGG orthologies of the cervical microbiota of statistical differences were identified between the HR-HPV infection and control women. Collectively, our study described the cervical microbiota and its potential function during HR-HPV infection. Biomarkers of cervical microbiota and the changed bacterial metabolic pathways and metabolites can help clarify the pathogenic mechanism of HR-HPV infection, making them promising targets for clinical treatment and intervention for HR-HPV infection and cervical carcinoma.